2018
DOI: 10.1088/1361-6471/aad53d
|View full text |Cite
|
Sign up to set email alerts
|

A nucleon–nucleus optical model for A ≤ 13 nuclei at 65–75 MeV projectile energy

Abstract: Small nuclei (A<16) test the limits of optical potential theory, most recently there has been difficulty matching the helium isotopes' analyzing powers at 71 MeV per nucleon. We provide a phenomenological optical potential that has been fit to a variety of experimental proton-nucleus and neutron-nucleus scattering data between A=4 and A=13 with a projectile energy between 65 and 75 MeV; the motivation being the helium isotopes. The resulting potential is dependent only on projectile isospin, neutron, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(20 citation statements)
references
References 51 publications
1
19
0
Order By: Relevance
“…Although in a much less significant way, the optical potentials also influence the shape of the parallel-momentum distribution. The n- 9 Be optical potential of Bonaccorso and Charity [44] produces a slightly less asymmetric peak than Weppner's [43]. Albeit not statistically significant, this hints at the influence of the n-T interaction in those reactions dynamics [52].…”
Section: Analysis Of the One-neutron Knockout From 11 Be And 15 Cmentioning
confidence: 75%
See 2 more Smart Citations
“…Although in a much less significant way, the optical potentials also influence the shape of the parallel-momentum distribution. The n- 9 Be optical potential of Bonaccorso and Charity [44] produces a slightly less asymmetric peak than Weppner's [43]. Albeit not statistically significant, this hints at the influence of the n-T interaction in those reactions dynamics [52].…”
Section: Analysis Of the One-neutron Knockout From 11 Be And 15 Cmentioning
confidence: 75%
“…For the first n- 9 Be interaction V 1 nT , we adopt the global optical potential developed by Weppner [43]. It has been fitted to elastic-scattering angular distributions and polarization data for a nucleon off a nucleus with mass number A 13 at energies between 65 and 75 MeV.…”
Section: Optical Potentialsmentioning
confidence: 99%
See 1 more Smart Citation
“…With the use of absorbed surface potential, Nodvik et al [11] reported the sets of parameters of WS and Gaussian potentials to analyze the differential cross sections at the bombarding energies from about 12 MeV to 20 MeV. Recently, the WS parameters have been updated via nucleon scattering upon light nuclei (A < 13) from 65 MeV to 75 MeV [10].…”
Section: Proton-nucleus Optical Potential In Folding Modelmentioning
confidence: 99%
“…For instance, the elastic scattering of proton from 12 C and 13 C targets at astrophysical energies is related to the first proton radiative capture reactions (p, γ) occurring in the carbon-nitrogen-oxygen (CNO) cycle in asymptotic giant branch (AGB) stars after the nucleus 12 C is formed by the 3α process. The mean-field potential models applied to these elastic scattering 12 C(p, p) and 13 C(p, p) are regularly of the WS form [10,11] with the parameters adjusted to obtain best fits in comparison with experimental data. Nevertheless, these phenomenological potential models are still relatively simple and depend on the parameters of a function instead of starting from NN interactions.…”
Section: Introductionmentioning
confidence: 99%